Fiber surface modified high-strength and high-ductility regenerated mortar printing ink material for building 3D printing and preparation method of fiber surface modified high-strength and high-ductility regenerated mortar printing ink material

By combining fiber surface modification technology and recycled sand, high-strength and high-ductility recycled mortar ink materials for building 3D printing have been developed, which solves the problems of unsustainability of fine aggregates and insufficient interface bonding performance in ECC, and achieves efficient improvement of materials and environmentally friendly applications.

CN119613048AInactive Publication Date: 2025-03-14TONGJI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411819648.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, most of the fine aggregates used in ECC are natural quartz sand. As an unsustainable resource, it is difficult to meet the growing demands of new infrastructure. At the same time, the interface bonding performance between fibers and substrates is insufficient, which affects the strength and ductility of ECC.

Method used

By modifying polyethylene fibers on the fiber surface by using polyvinylpyrrolidone to improve the interface bonding performance between the fiber and the matrix, and combining the high water absorption and skeleton effect of regenerated sand, a fiber surface modified high strength and high ductility regenerated mortar ink material for building 3D printing was developed.

Benefits of technology

It significantly improves the ductility and tensile strength of 3D printed concrete, improves the constructability and crack control capabilities of materials, enhances seismic resistance, and realizes high-value recycling of waste fibers, with good environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613048A_ABST
    Figure CN119613048A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber surface modified high-strength and high-ductility regenerated mortar printing ink material for building 3D printing and a preparation method thereof, and belongs to the technical field of building 3D printing and solid waste resource.The fiber surface modified high-strength and high-ductility regenerated mortar printing ink material is based on the strong interface-weak matrix principle, a fiber surface modification enhancing means and artificial defect regenerated sand fine aggregate are combined, and the fiber surface modified high-strength and high-ductility regenerated mortar printing ink material is prepared. The novel fiber surface modified high-strength and high-ductility regenerated mortar ink material for building 3D printing is developed, an effective method is provided for large-scale and high-value recovery of waste concrete, and good environmental benefits are shown. Compared with a common 3D printing concrete material, the 3D printing concrete has the advantages that the constructability, the crack control capability and the tensile strain capability of the 3D printing concrete can be obviously improved; and the ductility of the 3D printing component can be greatly improved, and the anti-seismic property of the structure is improved. The high-strength and high-ductility regenerated mortar printing ink material meeting the 3D printing requirements not only meets the requirements of digital and intelligent transformation and upgrading of the building industry and further promotes green and sustainable development of a novel construction mode, but also lays a certain foundation for industrial application of a 3D printing construction technology of the building industry in China, and has relatively high environmental and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building 3D printing and solid waste resource utilization, and in particular relates to a fiber surface modified high-strength and high-ductility recycled mortar ink material for building 3D printing and a preparation method thereof. Background Art

[0002] At present, my country's traditional construction industry is still a labor-intensive industry, and the level of automation in the construction industry is low, which is far from the requirements of industrialization and informatization. There are a series of problems in the development model of the construction industry, including low efficiency, high energy consumption, serious pollution, labor shortage and high environmental costs. In recent years, with the introduction of the concept of Industry 4.0, construction 3D printing technology has developed rapidly in the construction field, playing an important role in promoting the efficiency, ecology and intelligence of the construction process. At the same time, people have paid more and more attention to the sustainability of the building environment in the past few decades. Therefore, how to integrate the concept of sustainable development into the concept of 3D printing and realize the reuse of construction waste under the premise of protecting the environment and ecological safety has become a very important research content.

[0003] As the most utilized building material in the global urbanization process, concrete requires a large amount of natural gravel aggregate. According to data, it takes about 1,700-2,000 kilograms of aggregate to produce one cubic meter of concrete. Currently, the world needs 4 billion cubic meters of concrete each year, which means that 6-8 billion tons of fine and coarse aggregates need to be provided at the same time. In order to meet such a huge demand for aggregates, an important method is to crush and screen the construction solid waste after the demolition of old buildings, bridges, etc., and recycle them to eliminate construction solid waste and meet the aggregate needs of construction projects.

[0004] Recycled sand is a widely available and low-cost fine aggregate that can be obtained by crushing and screening waste concrete. The particle shape and microscopic characteristics of recycled sand are different from those of traditional quartz sand. It has a porous structure and multiple cracks, which will lead to a decrease in the mechanical properties of concrete and its application in traditional concrete is subject to certain restrictions. However, due to its porous structure and microcracks, recycled sand has the potential to be used in crack control of cement-based materials.

[0005] Engineered cementitious composites (ECC) with special ductility are fiber-reinforced concrete that exhibits strain hardening behavior and multiple cracking characteristics under tensile loads, with high tensile strain capacity (above 3%) and crack width control ability (below 0.1 mm). Researchers have used a variety of fibers to enhance the bridging effect of the matrix, including PE fibers with weak water absorption effect. However, the weak adsorption surface will weaken the bridging effect between the fiber and the matrix.

[0006] In summary, fine aggregate in ECC has not received much attention. Currently, most of the fine aggregate used in ECC is natural quartz sand, which is an unsustainable resource and may not be able to meet the growing demand for new infrastructure. And as an important bridging fiber that exerts the ductility of ECC, it also needs to be modified by effective means to enhance its interfacial bonding. Summary of the invention

[0007] In order to solve the above technical problems, the present invention proposes a fiber surface modified high-strength and high-ductility recycled mortar ink material and preparation method for building 3D printing. The present invention solves the problem that a large amount of construction solid waste cannot be effectively utilized, and at the same time greatly improves the constructability and ductility of 3D printed cement-based materials, which is conducive to 3D printing to achieve the performance requirements of concrete building vibration reduction and earthquake resistance.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] One of the technical solutions of the present invention:

[0010] A fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, composed of the following raw materials in parts by weight:

[0011] 100 parts of cement, 50-100 parts of fly ash, 10-30 parts of silica fume, 80-100 parts of regenerated sand, 1-3 parts of polyvinyl pyrrolidone modified polyethylene fiber, 0.5-1 parts of water reducer and 50-90 parts of water;

[0012] The modifier used in the polyvinyl pyrrolidone-modified polyethylene fiber is a polyvinyl pyrrolidone ethanol solution, and the concentration of the polyvinyl pyrrolidone ethanol solution is 3-5wt.%.

[0013] The present invention improves the interfacial bonding performance between the fiber and the matrix through fiber surface modification technology (i.e., adding polyvinyl pyrrolidone modified polyethylene fiber), thereby indirectly improving the seismic performance of 3D printed concrete by improving ductility and strength. Based on the principle of "strong interface-weak matrix", the present invention combines the fiber surface modification enhancement means with artificial defective recycled sand fine aggregate to develop a new fiber surface modified high-strength and high-ductility recycled mortar ink material for building 3D printing, which provides an effective method for large-scale and high-value recycling of waste concrete, showing good environmental benefits. And compared with ordinary 3D printing concrete materials, the recycled mortar ink material of the present invention can not only significantly improve the constructability, crack control and tensile strain capacity of 3D printed concrete; but also can greatly improve the ductility of 3D printed components and improve the seismic performance of structures. The high-strength and high-ductility recycled mortar ink material that meets the requirements of 3D printing of the present invention not only meets the requirements of digital transformation and upgrading of the construction industry, but also further promotes the green and sustainable development of new construction methods, and also lays a certain foundation for the industrial application of 3D printing construction technology in my country's construction industry, with high environmental and economic benefits.

[0014] Preferably, the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing is composed of the following raw materials, in parts by weight: 100 parts of cement, 50-80 parts of fly ash, 10-20 parts of silica fume, 80-90 parts of regenerated sand, 1-2 parts of polyvinyl pyrrolidone modified polyethylene fiber, 0.5-0.8 parts of water reducer and 50-80 parts of water.

[0015] More preferably, the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing is composed of the following raw materials, in parts by weight: 100 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 90 parts of regenerated sand, 2 parts of polyvinyl pyrrolidone-modified polyethylene fiber, 0.8 parts of water reducer and 80 parts of water.

[0016] The preparation method of the polyvinyl pyrrolidone modified polyethylene fiber is as follows: polyethylene fiber (PE fiber) is washed with anhydrous ethanol and deionized water, dried, the dried polyethylene fiber is immersed in a polyvinyl pyrrolidone ethanol solution, firstly subjected to ultrasonic treatment, then immersed, the immersed polyethylene fiber is washed with anhydrous ethanol and deionized water, dried, and the polyvinyl pyrrolidone modified polyethylene fiber is obtained.

[0017] The present invention adopts a method of modifying polyethylene fiber with polyvinyl pyrrolidone (PVP) to improve the adhesion between the interface of PE fiber and matrix, thereby improving the bridging effect of ECC and further enhancing its strength and ductility. Specifically: (1) PVP is a polymer compound with a high molecular weight and polar groups, which can dissolve in water and form a high viscosity solution. The PVP molecule contains a pyrrole ring structure, which forms a uniform adsorption layer between it and the active groups on the surface of the PE fiber. The adsorption layer helps to improve the charge distribution on the surface of the PE fiber, reduce the repulsive effect between the fibers, and enable the fibers to better disperse stress when subjected to external forces, thereby improving the strength and toughness of the fibers. (2) PVP molecules have good hydrophilicity in aqueous solution and can hydrate with water molecules to form a hydration layer, which helps to enhance the interaction between the fiber and the matrix, making it difficult for the fiber to be pulled out of the matrix or broken when subjected to external forces, thereby improving the overall strength and toughness of the ECC.

[0018] In order to further expand the application scenarios of 3D printed concrete buildings, the present invention provides a green, environmentally friendly, high-strength and high-ductility 3D printed concrete ink material, which integrates recycled aggregate (i.e. recycled sand, the same below) and surface modification technology with 3D printed concrete technology, and utilizes the "strong interface-weak matrix" principle to help improve the ductility and seismic resistance of 3D printed structural components, with significant environmental and economic benefits.

[0019] The molecular weight of the polyethylene fiber is ≥ 3 million, the fiber length is 6-18 mm, the fiber strength is 2.8-4 N / tex, and the tensile strength is ≥ 2 GPa. The polyethylene fiber used in the present invention is an ultra-high molecular weight polyethylene fiber, wherein the fiber strength and tensile strength are tested according to the American standard ASTM D3822: Standard Test Method for Tensile Properties of Single Textile Fibers; and / or

[0020] The polyvinyl pyrrolidone is K90 grade polyvinyl pyrrolidone.

[0021] The cement is Portland cement; and / or

[0022] The fly ash is any one of Class I fly ash and Class II fly ash; and / or

[0023] The SiO2 content in the silica ash is above 90wt.%; and / or

[0024] The regenerated sand is fine aggregate with a particle size of 0.075-1.18 mm after grinding of construction waste; and / or

[0025] The water reducing agent is a polycarboxylic acid water reducing agent.

[0026] The construction waste is a mixture of waste concrete and waste bricks and tiles, and the mass ratio of the two is 1:1.

[0027] The present invention adopts a suitable method to improve the bonding performance of the interface between the PE fiber and the matrix, which will help to improve the bridging effect of the ECC and further enhance its strength and ductility.

[0028] The second technical solution of the present invention:

[0029] The present invention also provides a method for preparing the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, comprising the following steps:

[0030] (1) accurately weighing the raw materials according to the weight ratio, mixing cement, fly ash and silica fume, stirring, and adding water and stirring again to obtain a first mixture;

[0031] (2) adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of a water reducing agent, and stirring to obtain a second mixture;

[0032] (3) Adding polyvinyl pyrrolidone-modified polyethylene fibers to the second mixture in batches, and adding the remaining water reducer, and stirring, to obtain the fiber surface-modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing.

[0033] In step (1), the stirring speed is 100-300 rpm, the stirring time after mixing cement, fly ash and silica fume is 1 minute, and the stirring time after adding water is 2-3 minutes.

[0034] In step (2), the stirring speed is 100-300 rpm, and the stirring time is 2-4 minutes.

[0035] When the regenerated sand is in a dry state, additional water is added according to the water absorption rate of the regenerated sand to adjust the regenerated sand to a saturated surface dry state; when the regenerated sand is in a saturated surface dry state, no adjustment is required.

[0036] In step (2), the partial water reducer accounts for 85-90% of the total mass of the water reducer.

[0037] In step (3), the stirring speed is 300-500 rpm and the stirring time is 5-7 minutes to ensure that the polyvinyl pyrrolidone-modified polyethylene fibers are evenly distributed.

[0038] In step (3), the polyvinyl pyrrolidone-modified polyethylene fibers are added in batches of 3-4.

[0039] The third technical solution of the present invention:

[0040] The present invention also provides the application of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing in the field of 3D printing building materials.

[0041] The present invention organically combines recycled aggregate with 3D printing concrete technology, which can not only improve the vibration reduction and earthquake resistance of 3D printed buildings and lay the foundation for their popularization and application, but also make full use of the huge stock of recycled aggregate as building materials to fill the increasingly scarce non-renewable resources, thereby bringing considerable benefits in terms of economy and ecology.

[0042] Compared with the prior art, the present invention has the following advantages and technical effects:

[0043] (1) The fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing provided by the present invention is a 3D printing cement-based material. Due to its extrusion and layer-by-layer stacking construction method, when the material is extruded along the nozzle by the stirring screw, part of the incorporated ultra-high molecular weight polyethylene fibers are distributed along the printing direction, and more fibers are distributed on the same cross-section, which can significantly improve the tensile strength and tensile strain capacity of the ink material.

[0044] (2) In the method of the present invention, due to the mechanical crushing process in the production process of recycled aggregate, the old residual mortar often exhibits porosity and some microcracks exist on the surface of the aggregate, which will lead to the random development of cracks in the ECC matrix during the tensile process, promote the growth of the ductility of the cement-based material, and form an ultra-high ductility ECC.

[0045] (3) Since the hydrophobicity of PE fiber hinders its bonding with the matrix, the present invention uses polyvinyl pyrrolidone to modify the surface of PE fiber, thereby enhancing the interfacial bonding between PE fiber and cement paste and improving the bonding performance of the interface transition zone between fiber and mortar matrix.

[0046] (4) In the method of the present invention, due to the high water absorption and skeleton effect of the regenerated sand, the static yield stress of the mortar is enhanced, which is beneficial to the development of the early constructibility of the 3D printing ink material during the layer-by-layer stacking process.

[0047] (5) In the method of the present invention, the coupling effect of the weak matrix and strong interface formed by the regenerated sand and the fiber is beneficial to further improve the strength and ductility of the cement-based material. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0049] Figure 1The mechanical properties test results of the specimens of Example 1 and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION

[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0051] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0055] The saturated surface dry state means that all the pores inside the material are saturated with water, but there is no moisture on the surface. Aggregates in the saturated surface dry state neither absorb moisture from the concrete nor release moisture to the concrete mixture, which is conducive to strict control of the water consumption of concrete.

[0056] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0057] All raw materials used in the examples of the present invention are commercially available.

[0058] Unless otherwise specified, the “parts” used in the embodiments of the present invention are “parts by weight”.

[0059] It should be pointed out that the matters not described in detail in the present invention are all conventional operating methods in the field and are not the focus of the present invention. For example, the specific preparation method of polyvinyl pyrrolidone ethanol solution and the specific method of standard maintenance are all completed by conventional methods.

[0060] The technical solution of the present invention is further illustrated by the following embodiments.

[0061] Example 1

[0062] The present embodiment provides a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, which is prepared from the following raw materials, in parts by weight: 100 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 90 parts of regenerated sand, 2 parts of polyvinyl pyrrolidone-modified polyethylene fiber, 0.8 parts of water reducer and 80 parts of water.

[0063] Among them, the cement is PO 52.5 ordinary Portland cement; the fly ash is Class I low-calcium fly ash (purchased from Shanghai Siqi Building Materials Co., Ltd.); the SiO2 content in the silica ash is 98wt.%; the regenerated sand is crushed from waste concrete and waste bricks and tiles (mass ratio is 1:1), with a particle size of 0.075-1.18mm, and is in a saturated surface dry state; the water reducer is CQJ-JSS02 type polycarboxylic acid series high-efficiency water reducer; and the water is tap water.

[0064] The preparation method of polyvinyl pyrrolidone modified polyethylene fiber is as follows: a polyethylene fiber with a molecular weight of 3 million (length of 12 mm, fiber strength of 3.2 N / tex, and tensile strength of 2.1 GPa) is washed 3 times with anhydrous ethanol and deionized water respectively to remove surface impurities, and then dried. The dried polyethylene fiber is immersed in a polyvinyl pyrrolidone ethanol solution with a concentration of 3wt.%, first ultrasonically treated for 15 minutes, and then immersed for 30 minutes, and the immersed polyethylene fiber is washed 3 times with anhydrous ethanol and deionized water respectively, and then dried at 50°C for 4 hours to obtain a polyvinyl pyrrolidone modified polyethylene fiber, wherein the polyvinyl pyrrolidone is K90 grade polyvinyl pyrrolidone.

[0065] Preparation method of the above-mentioned fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing:

[0066] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume, stirring at a speed of 200 rpm for 1 minute, and adding water and stirring at a speed of 200 rpm for 3 minutes to obtain a first mixture;

[0067] Step 2: adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 85% of the total mass of the water reducer), and stirring at a speed of 300 rpm for 4 minutes to obtain a second mixture;

[0068] Step three, adding polyvinyl pyrrolidone-modified polyethylene fibers into the second mixture in three batches, adding the remaining water reducer at the same time, stirring at a speed of 500 rpm for 5 minutes, and obtaining a fiber surface-modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing.

[0069] Example 2

[0070] The present embodiment provides a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, which is prepared from the following raw materials, in parts by weight: 100 parts of cement, 50 parts of fly ash, 30 parts of silica fume, 80 parts of regenerated sand, 1 part of polyvinyl pyrrolidone modified polyethylene fiber, 0.5 parts of water reducer and 90 parts of water.

[0071] Among them, the cement is PO 52.5 ordinary Portland cement; the fly ash is Class I low-calcium fly ash (purchased from Shanghai Siqi Building Materials Co., Ltd.); the SiO2 content in the silica ash is 90wt.%; the regenerated sand is crushed from waste concrete and waste bricks and tiles (mass ratio is 1:1), with a particle size of 0.075-1.18mm, and is in a saturated surface dry state; the water reducer is CQJ-JSS02 type polycarboxylic acid series high-efficiency water reducer; and the water is tap water.

[0072] The preparation method of polyvinyl pyrrolidone modified polyethylene fiber is the same as that in Example 1.

[0073] The preparation method of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing in this embodiment is the same as that in Example 1.

[0074] Example 3

[0075] The present embodiment provides a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, which is prepared from the following raw materials, in parts by weight: 100 parts of cement, 100 parts of fly ash, 10 parts of silica fume, 100 parts of regenerated sand, 3 parts of polyvinyl pyrrolidone-modified polyethylene fiber, 1 part of water reducer and 60 parts of water.

[0076] Among them, the cement is PO 52.5 ordinary Portland cement; the fly ash is Class II fly ash (purchased from Shanghai Siqi Building Materials Co., Ltd.); the SiO2 content in the silica ash is 95wt.%; the regenerated sand is crushed from waste concrete and waste bricks and tiles (mass ratio is 1:1), with a particle size of 0.075-1.18mm, and is in a saturated surface dry state; the water reducer is CQJ-JSS02 type polycarboxylic acid series high-efficiency water reducer; and the water is tap water.

[0077] The preparation method of polyvinyl pyrrolidone modified polyethylene fiber is the same as that in Example 1.

[0078] The preparation method of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing in this embodiment is the same as that in Example 1.

[0079] Example 4

[0080] This embodiment provides a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing. The raw materials and proportions are the same as those in Example 1, and the preparation method is as follows:

[0081] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume, stirring at a speed of 100 rpm for 1 minute, and adding water and stirring at a speed of 300 rpm for 3 minutes to obtain a first mixture;

[0082] Step 2: adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 90% of the total mass of the water reducer), and stirring at a speed of 100 rpm for 4 minutes to obtain a second mixture;

[0083] Step three, adding polyvinyl pyrrolidone-modified polyethylene fibers into the second mixture in three batches, adding the remaining water reducer at the same time, stirring at a speed of 300 rpm for 7 minutes, and obtaining a fiber surface-modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing.

[0084] Example 5

[0085] This embodiment provides a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing. The raw materials and proportions are the same as those in Example 1, and the only difference is that the preparation method is:

[0086] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume, stirring at a speed of 300 rpm for 1 minute, and adding water and stirring at a speed of 200 rpm for 2 minutes to obtain a first mixture;

[0087] Step 2: adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 90% of the total mass of the water reducer), and stirring at a speed of 200 rpm for 3 minutes to obtain a second mixture;

[0088] Step three, adding polyvinyl pyrrolidone-modified polyethylene fibers into the second mixture in four batches, adding the remaining water reducer at the same time, stirring at a speed of 300 rpm for 5 minutes, and obtaining a fiber surface-modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing.

[0089] Example 6

[0090] The ratio and preparation method of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing are the same as those in Example 1, except that the preparation method of the polyvinyl pyrrolidone-modified polyethylene fiber is as follows: a polyethylene fiber with a molecular weight of 3 million (length 12 mm, fiber strength 3.2 N / tex, tensile strength 2.1 GPa) is washed 3 times with anhydrous ethanol and deionized water to remove surface impurities, and then dried. The dried polyethylene fiber is immersed in a polyvinyl pyrrolidone ethanol solution with a concentration of 5 wt.%, first ultrasonically treated for 15 minutes, and then immersed for 30 minutes. The immersed polyethylene fiber is washed 3 times with anhydrous ethanol and deionized water, and then dried at 50° C. for 4 hours to obtain a polyvinyl pyrrolidone-modified polyethylene fiber, wherein the polyvinyl pyrrolidone is K90 grade polyvinyl pyrrolidone.

[0091] The performance of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing prepared in Examples 2-6 is not significantly different from that in Example 1.

[0092] Comparative Example 1

[0093] A fiber-reinforced ink material without regenerated sand is prepared from the following raw materials, measured in parts by weight: 100 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 90 parts of natural sand, 2 parts of polyvinyl pyrrolidone-modified polyethylene fiber, 0.8 parts of a water reducer and 80 parts of water.

[0094] Among them, the cement is PO 52.5 ordinary Portland cement; the fly ash is Class I low-calcium fly ash; the SiO2 content in the silica ash is 98wt.%; the natural sand is quartz sand with a particle size range of 0.075-1.18mm; the water reducer is CQJ-JSS02 type polycarboxylic acid series high-efficiency water reducer; and the water is ordinary tap water.

[0095] The preparation method of polyvinyl pyrrolidone modified polyethylene fiber is the same as that in Example 1.

[0096] The preparation method of the fiber-reinforced ink material without regenerated sand is as follows:

[0097] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume evenly, stirring at a speed of 200 rpm for 1 minute, and adding water and stirring at a speed of 200 rpm for 3 minutes to obtain a first mixture;

[0098] Step 2, adding natural sand to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 85% of the total mass of the water reducer), stirring at a speed of 300 rpm for 4 minutes to obtain a second mixture;

[0099] Step three, adding polyvinyl pyrrolidone-modified polyethylene fibers into the second mixture in three batches, adding the remaining water reducer at the same time, stirring at a speed of 500 rpm for 5 minutes, and obtaining a fiber-reinforced ink material free of regenerated sand.

[0100] Comparative Example 2

[0101] The invention discloses an unmodified 3D printed recycled sand fiber reinforced concrete, which is prepared from the following raw materials, measured in parts by weight: 100 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 90 parts of recycled sand, 2 parts of polyethylene fiber, 0.8 parts of water reducer and 80 parts of water.

[0102] Among them, the cement is PO 52.5 ordinary Portland cement; the fly ash is Class I low-calcium fly ash; the silica fume SiO2 content is 98%; the regenerated sand is crushed from waste concrete and waste bricks and tiles (mass ratio is 1:1), with a particle size of 0.075-1.18mm, and is in a saturated surface dry state; the molecular weight of the polyethylene fiber is 3 million, the length is 12mm, the fiber strength is 3.2N / tex, and the tensile strength is 2.1GPa; the water reducer is CQJ-JSS02 type polycarboxylic acid series high-efficiency water reducer; the water is tap water.

[0103] The preparation method of the above-mentioned unmodified 3D printed recycled sand fiber reinforced concrete comprises the following steps:

[0104] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume, stirring at a speed of 200 rpm for 1 minute, and adding water and stirring at a speed of 200 rpm for 3 minutes to obtain a first mixture;

[0105] Step 2: adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 85% of the total mass of the water reducer), and stirring at a speed of 300 rpm for 4 minutes to obtain a second mixture;

[0106] Step three, adding polyethylene fibers into the second mixture in three batches, adding the remaining water reducer at the same time, stirring at a speed of 500 rpm for 5 minutes, and obtaining an unmodified 3D printing recycled sand fiber reinforced concrete ink material.

[0107] Comparative Example 3

[0108] A weakly modified fiber reinforced 3D printing concrete ink material is prepared from the following raw materials, measured in parts by weight: 100 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 90 parts of regenerated sand, 2 parts of polyvinyl pyrrolidone modified polyethylene fiber, 0.8 parts of water reducer and 80 parts of water.

[0109] Wherein, the types of cement, fly ash, silica fume, regenerated sand, water reducing agent and water are the same as those in Example 1.

[0110] The preparation method of polyvinyl pyrrolidone modified polyethylene fiber is as follows: a polyethylene fiber with a molecular weight of 3 million (length of 12 mm, fiber strength of 3.2 N / tex, and tensile strength of 2.1 GPa) is washed 3 times with anhydrous ethanol and deionized water respectively to remove surface impurities, and then dried. The dried polyethylene fiber is immersed in a polyvinyl pyrrolidone ethanol solution with a concentration of 1 wt.%, first ultrasonically treated for 15 minutes, and then immersed for 30 minutes. The immersed polyethylene fiber is washed 3 times with anhydrous ethanol and deionized water respectively, and then dried at 50° C. for 4 hours to obtain a polyvinyl pyrrolidone modified polyethylene fiber, wherein the polyvinyl pyrrolidone is K90 grade polyvinyl pyrrolidone.

[0111] The preparation method of the above-mentioned weakly modified fiber reinforced 3D printing concrete ink material is:

[0112] Step 1, accurately weighing each raw material according to the weight ratio, mixing cement, fly ash and silica fume, stirring at a speed of 200 rpm for 1 minute, and adding water and stirring at a speed of 200 rpm for 3 minutes to obtain a first mixture;

[0113] Step 2: adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of the water reducer (the portion of the water reducer is 85% of the total mass of the water reducer), and stirring at a speed of 300 rpm for 4 minutes to obtain a second mixture;

[0114] Step three, adding the polyvinyl pyrrolidone-modified polyethylene fiber into the second mixture in three batches, adding the remaining water reducer at the same time, stirring at a speed of 500 rpm for 5 minutes, and obtaining a weakly modified fiber-reinforced 3D printing concrete ink material.

[0115] The ink materials prepared in Example 1 and Comparative Examples 1 to 3 were respectively printed or mixed and cast layer by layer according to the set printing program to obtain dumbbell-shaped tensile specimens with a tensile section length of 80 mm and a width of 15 mm, and were standardly cured in a standard curing room for 28 days.

[0116] The ductility test of the direct tensile test was carried out on the above-mentioned embodiment and comparative example specimens, referring to the standard of Japan Society of Civil Engineers (JSCE, 2008), and the test conditions of all dumbbell-type tensile specimens were exactly the same. The test results are shown in Table 1 and Figure 1 shown.

[0117] Table 1 Mechanical properties test results

[0118]

[0119] Based on the test results in Table 1, it can be seen that compared with the 3D printing recycled mortar without fiber modification, its tensile strain and tensile strength increased by 62.5% and 36.5%, respectively. Compared with the 3D printing mortar without recycled sand, its tensile strain and tensile strength increased by 81.6% and 28.9%, respectively. That is to say, the "strong interface-weak matrix" coupling effect of fiber modification and weak recycled mortar matrix significantly improves the tensile strain capacity of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing prepared in Example 1. The ductility index (i.e., tensile strain capacity) of a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing proposed by the present invention is significantly better than that of the control group (Comparative Examples 1-Comparative Examples 3), and the tensile strength is also improved, which greatly improves the strength and ductility of 3D printed concrete, and has good application prospects in improving the seismic performance of 3D printed structural components. The fiber surface modification method is effective and has a wide range of application scenarios, and can be extended to other similar fiber materials with weak water absorption. At the same time, the application of recycled fine aggregate improves the buildability of mortar and greatly enhances the sustainability of 3D printed buildings, further promoting the application of 3D printing construction technology in my country's construction industry, with high environmental benefits and structural performance.

[0120] In summary, the present invention has achieved at least the following technical effects:

[0121] (1) Significantly improve ductility and tensile strength: Through the application of fiber surface modification technology and the "strong interface-weak matrix" principle, the present invention significantly improves the ductility and tensile strength of 3D printed concrete.

[0122] (2) Improved buildability and crack control capabilities: The optimized preparation process and raw material selection make the 3D printing process more stable and controllable, improving the buildability and crack control capabilities of the material.

[0123] (3) Enhanced seismic performance and environmental friendliness: By improving the overall performance of the material and the high-value recovery of waste fibers, the present invention not only enhances the seismic performance of 3D printed buildings, but also further improves environmental friendliness and economy.

[0124] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing, characterized in that: In parts by weight, it is composed of the following raw materials: 100 parts of cement, 50-100 parts of fly ash, 10-30 parts of silica fume, 80-100 parts of regenerated sand, 1-3 parts of polyvinyl pyrrolidone modified polyethylene fiber, 0.5-1 parts of water reducer and 50-90 parts of water; The modifier used in the polyvinyl pyrrolidone-modified polyethylene fiber is a polyvinyl pyrrolidone ethanol solution, and the concentration of the polyvinyl pyrrolidone ethanol solution is 3-5wt.%.

2. The fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 1, characterized in that: The preparation method of the polyvinyl pyrrolidone modified polyethylene fiber is as follows: the polyethylene fiber is washed with anhydrous ethanol and deionized water, dried, the dried polyethylene fiber is immersed in a polyvinyl pyrrolidone ethanol solution, firstly subjected to ultrasonic treatment, then immersed, the immersed polyethylene fiber is washed with anhydrous ethanol and deionized water, dried, and the polyvinyl pyrrolidone modified polyethylene fiber is obtained.

3. The fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 2, characterized in that: The polyethylene fiber has a molecular weight of ≥ 3 million, a fiber length of 6-18 mm, a fiber strength of 2.8-4 N / tex, and a tensile strength of ≥ 2 GPa; and / or The polyvinyl pyrrolidone is K90 grade polyvinyl pyrrolidone.

4. The fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 1, characterized in that: The cement is Portland cement; and / or The fly ash is any one of Class I fly ash and Class II fly ash; and / or The SiO2 content in the silica ash is above 90wt.%; and / or The regenerated sand is fine aggregate with a particle size of 0.075-1.18 mm after grinding of construction waste; and / or The water reducing agent is a polycarboxylic acid water reducing agent.

5. A method for preparing a fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) accurately weighing the raw materials according to the weight ratio, mixing cement, fly ash and silica fume, stirring, and adding water and stirring again to obtain a first mixture; (2) adding the regenerated sand in a saturated surface dry state to the first mixture, and adding a portion of a water reducing agent, and stirring to obtain a second mixture; (3) Adding polyvinyl pyrrolidone-modified polyethylene fibers to the second mixture in batches, and adding the remaining water reducer, and stirring, to obtain the fiber surface-modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing.

6. The method for preparing the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 5, characterized in that: In step (1), the stirring speed is 100-300 rpm, the stirring time after mixing cement, fly ash and silica fume is 1 minute, and the stirring time after adding water is 2-3 minutes.

7. The method for preparing the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 5, characterized in that: In step (2), the stirring speed is 100-300 rpm, and the stirring time is 2-4 minutes.

8. The method for preparing the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 5, characterized in that: In step (2), the partial water reducer accounts for 85-90% of the total mass of the water reducer.

9. The method for preparing the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to claim 5, characterized in that: In step (3), the stirring speed is 300-500 rpm and the stirring time is 5-7 minutes; and / or The polyvinyl pyrrolidone modified polyethylene fiber is added in 3-4 batches.

10. Application of the fiber surface modified high-strength and high-ductility recycled mortar ink material for architectural 3D printing according to any one of claims 1 to 4 in the field of 3D printing building materials.

Citation Information

Patent Citations

  • Reclaimed sand-doped ultrahigh-ductility cement-based ink material as well as preparation method and application thereof

    CN117185741A

  • Green high-durability marine concrete and preparation method thereof

    CN118812208A